Gestión de los residuos sólidos urbanos y su influencia en el grado de satisfacción de pobladores del mercado Modelo, Iquitos 2018 - Mass Soplin, Jose Raul (2022)
The present investigation sought to determine the level of incidence of urban solid waste management in the degree of satisfaction of the inhabitants of the Bethlehem market - uptown, Iquitos 2019. The research was descriptive - non-experimental correlational, with a simple evaluation, based on systematic data collection, using a questionnaire as an instrument. The villagers were randomly selected from 120 homes adjacent to the Bethlehem market - uptown, and applying the sample formula, a sample of 68 homes to be surveyed was obtained. The results obtained show us that in the management of urban solid waste in the degree of satisfaction of the inhabitants of the market of Bethlehem-High Zone, Iquitos 2019, there is a high incidence with the degree of satisfaction since having an appropriate management of urban solid waste the user shows satisfaction to the fulfillment of this essential health service, which confirms the hypothesis raised. Regarding the level of incidence of solid waste planning, there is a 49.64% acceptance by the surveyed user. The level of incidence of solid waste management shows us a result of 90% dissatisfaction by the user surveyed. Regarding the level of incidence of the execution of urban solid waste, 71% approval is obtained by the user surveyed. Finally, in relation to the level of incidence of solid waste control, a 75% disapproval result is obtained by the surveyed user.